Spatial Repolarization Heterogeneity and Survival in Chagas Disease - Sassi, R.; Rivolta, M. W.; Mainardi, L. T.; Reis, R. C.; Rocha, M. O. C.; Ribeiro, A. L. P.; Lombardi, F. (Methods of Information in Medicine, 2014)
Objectives: We investigated if cardiac spatial repolarization heterogeneity might be associated with an increased risk of death in patients with chronic Chagas disease.Methods: Repolarization heterogeneity was assessed using the V-index, a recently introduced metric founded on a biophysical model of the ECG. This metric provides an estimate of the standard deviation of the repolarization times across the heart. We analyzed 113 patients (aged 21– 67 years) enrolled between 1998 and 1999 who had a known serological status showing positive reactions to Trypanosoma cruzi. Fourteen subjects died during a 10-year follow-up period.Results: The V-index was significantly lower in survivor (S) than in non-survivor (NS) subjects (S: 31.2 ± 13.3 ms vs NS: 41.2 ± 18.6 ms, single-tail t-test: p = 0.009, single-tail Wilcoxon rank sum test: p = 0.029). A V-index larger than 36.3 ms was related to a significantly higher risk of death in a univariate Cox proportional-hazards analysis (hazard ratio, HR = 5.34, p = 0.0046). In addition, V-index > 36.3 ms retained its prognostic value in a multivariate Cox proportional-hazards analysis after adjustment for other three clinical variables (left ventricular ejection factor < 0.50, QRS duration > 133 ms, ventricular tachycardia during stress testing or 24 hours Holter) and for T-wave amplitude variability > 30 μV, even using shrinkage, a statistical procedure that protects against over-fitting due to small sample size.Conclusions: The study showed that an increased dispersion of repolarization times in patients with Chagas disease, as measured by the V-index, is significantly correlated with the risk of death in a univariate survival analysis. The V-index captures prognostic information not immediately available from the analysis of other established risk factors.
Keywords: Chagas disease; Chagas cardiomyopathy; ambulatory electrocardiography; digital signal processing; electrophysiological processes; ventricular fibrillation